1997
DOI: 10.1074/jbc.272.45.28289
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal Subdomain Makes an Important Contribution to the DNA Binding Activity of the Pax-3 Paired Domain

Abstract: The recognition of DNA targets by Pax-3 is achieved through the coordinate use of two distinct helix-turnhelix-based DNA-binding modules: a paired domain, composed of two structurally independent subdomains joined by a short linker, and a paired-type homeodomain. In mouse, the activity of the Pax-3 paired domain is modulated by an alternative splicing event in the paired domain linker region that generates isoforms (Q ؉ and Q ؊ ) with distinct C-terminal subdomain-mediated DNA-binding properties. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…Although the N-terminal PAI has been noted in some cases to be the most critical subdomain, another study provides compelling evidence that the recognition of DNA targets by Pax proteins is achieved through the coordinate use of both subdomains. 19 Indeed, our demonstration of abrogation of DNA binding by a substitution mutation region within the C-subdomain supports the notion that this region plays a crucial role in the normal activities of the PAX9 paired domain. Our analysis of the paired domains of other members of the PAX gene family revealed another human genetic disorder caused by mutation of the equivalent Ile87 residue.…”
Section: Discussionsupporting
confidence: 64%
“…Although the N-terminal PAI has been noted in some cases to be the most critical subdomain, another study provides compelling evidence that the recognition of DNA targets by Pax proteins is achieved through the coordinate use of both subdomains. 19 Indeed, our demonstration of abrogation of DNA binding by a substitution mutation region within the C-subdomain supports the notion that this region plays a crucial role in the normal activities of the PAX9 paired domain. Our analysis of the paired domains of other members of the PAX gene family revealed another human genetic disorder caused by mutation of the equivalent Ile87 residue.…”
Section: Discussionsupporting
confidence: 64%
“…The side chain carbonyl of residue 121 makes a water-mediated contact to base 19. The Ser-121 side chain may also make a similar contact as it has been shown that the C subdomain of Pax3 has DNA selectivity similar to that of Pax6 (Vogan and Gros 1997). Given the conservation of the C subdomain and the similar DNA-binding specificities of many paired domains, the Pax6 structure may provide a good basis for modeling DNA contacts by the C subdomain in other Pax proteins.…”
Section: Basis For Dna Recognition By the Pax C Subdomainmentioning
confidence: 97%
“…Although this domain is not believed to play a critical role in DNA binding, current structural models suggest that it is in close proximity to DNA (25). In addition, alternative splicing of a glutamine residue at position 108 of Pax3/Pax7 is known to alter DNA binding specificity of the PD (54,58). Therefore, mutants Xa100 should be ideally suited to monitor structural changes associated with DNA binding by the PD.…”
Section: Discussionmentioning
confidence: 99%